Effect of genetic group of sire and dam and number of inseminations on conception rate in crossbred cows - ULEMALE, A H; KULKARNI, M D; KHANVILKAR, A V; BANSOD, R S (The Indian Journal of Animal Reproduction, 2023)
The study revealed that effect of genetic group of sire and dam on conception rate was non-significant (P > 0.05). About 80% females got conceived with maximum number of four inseminations.